SARS-CoV-2 presencia de comorbilidades y manifestaciones clínicas en internos de medicina y enfermería de la Universidad Nacional de Loja - Cárdenas Veintimilla, José Paúl (2022)
The severe acute respiratory syndrome-related coronavirus (SARS-CoV-2) pandemic, which causes coronavirus disease 2019 (COVID-19), emerged in late 2019 in Wuhan, Hubei province, China. It is a descriptive study, with a quantitative approach, observational type, prospective cross-sectional cohort, made up of a population of 132 medical and nursing students. The objective of this study was to identify the presence of comorbidities and their relationship with clinical manifestations against SARS-CoV-2 in medicine and nursing interns at the National University of Loja, from September to June 2021. The results obtained in the present study show that the main comorbidity is given by diabetes, which represents 3.8%, followed by cardiovascular diseases with 1.27%, with the absence of cancer within the main comorbidities. SARS-CoV-2 antibody levels were positive in 9.85% of the population and 90.15% negative, where 13.89% of all women are positive, and 8.33% of men of all men are positive. Among the main clinical manifestations that the patients with a positive result had, it was evidenced that the most prevalent was fever, which corresponds to 76.92% of the population, followed by the presence of cough represented by 61.54%, then it was find fatigue with 46.15%; then there is headache and myalgia with 30.77%; then we found the presence of sputum and anorexia with 23.08%; rhinorrhea, ageusia and anosmia represent the same percentage 15.38%, and in the end we find headache, sore throat, arthralgia and diarrhea, with 7.69% individually, conjunctivitis and pain or pressure sensation in the chest being absent, which were some of the manifestations taken into account due to the variety of possible symptoms